TRAUMATIC NECK INJURIES IDENTIFIED BY CONVENTIONAL X-RAY IMAGING-AN AUTOPSY CASE REPORT - Jankova, Renata; Mitrevski, Zoran (Journal of Morphological Sciences, 2023)
Traumatic injuries of the neck in violent death cases are not so common finding in autopsy examination such as traumatic head injuries that may have caused or contributed to death. Nevertheless, forensic examination of the neck structures must be done thoroughly as well as examination of other parts of the body, especially when there is a particular indication for suspected serious injury in the neck region such as fractures of the cervical vertebrae or dislocations due to ligamentous separation. External inspection of the neck is quite simple in comparison to internal examination. Even after anterior and posterior preparation of the soft tissue layers of the neck region, all parts of the upper cervical vertebrae are not easily accessible for examination. In such cases, a radiographic examination is indicated for displaying and localizing possible dislocations or fractures of the neck. In this paper we present an autopsy case where upper cervical vertebrae fractures detected by post mortem X-ray imaging were the clue for solving the cause and manner of death. An accurate forensic approach of the case is necessary since it has medico-legal importance in aspect of gathering all possible evidence to verify the injuries that may caused, or contributed to, death. Key words: post mortem examination, upper cervical vertebrae fractures, X-ray imaging.